The Impact of Financial Inclusion on Economic Growth, Poverty, Income Inequality, and Financial Stability in Asia - RATNAWATI, Kusuma (The Journal of Asian finance, economics, and business, 2020)
As an effort to achieve sustainable development and increase people’s welfare, financial inclusion has become the policy agenda of many countries. Therefore, the effect of financial inclusion on economic growth, poverty, income inequality, and financial stability in several countries in Asia has become the goal and this is the subject of this study. Financial inclusion is measured by 3 dimensions, namely banking penetration, access to banking services, and use of banking services. Poverty ratio below the national poverty line and the Gini coefficient are used as indicators of poverty and income inequality. Financial stability is measured by Bank Z-Score and bank nonperforming loans. The results from the hypothesis test shows that all dimensions of financial stability simultaneously have significant influence on economic growth, poverty, income inequality, and financial stability. On the other hand, the partial impact of financial inclusion dimension on economic growth, poverty alleviation, income inequality, and financial stability in ten countries of Asia has not been optimal. The derived results of this study is required to be interpreted and considered by the Governments of each country in developing strategies for increasing financial inclusion, so that the policy to achieve sustainable development and enhancement of people’s welfare can be achieved.